Pengaruh Sumber Daya dan Kapabilitas Terhadap Keunggulan Posisi - Solihat, Ani (Universitas Pendidikan Indonesia, 2011)
Competition is not just university level but at the program of study level, this shows that program of study is a business unit of the university or as a basic unit of analysis in creating a college of excellence. The competition that occurred between programs of study in increasing market share through new admissions, the more has the advantage of the growing number of enthusiasts, so a program of study are required to have a fascination with power so that the positioning advantage program of study in superior universit.The purpose of reasearch was to determine what factors are affecting the position advantage especially program of study management in Bandung, especially tangible resources (physical and technological) and intangible resources (organization, human resources, and reputation) as well as through the capabilities of the program study.Program of study in university which has the position advantage that means resources and capabilitie have a uniqueness that is hard to duplicate. Resources is anything owned or cotroled by program of study, which could br throught of as strength or weakness and capabilities is the management ability to deploy resourcesThe method used in this study is a survey research method explanations (explanatory survey) with a sampling technique was purposive rather nonprobabilistik (purposial sampling) is a technique that sample been intentionally set by the researchers on certain criteria and considerations. Processing data using path analysis with the structure variables of resources, capabilities and position advantages.The results showed program of study management in Bandung University was available of tangible resource and intangible resources are with a good show and capabilities is already well and has shown the positioning advantage.Result of hypothesis test between exogenous and endogenous variables showed that the influence of resources and capabilities to position advantage at 18.521, while partially accepted H0 respectively, indicating the resources and capabilities is partially not significantly influence the position advantage, while the hypothesis II indicates the value of path coefficients (18.219) and hypothesis III 13.955 this valuable resource shows the tangible and intangible resources and capabilities to simultaneously affect the positioning advantage.Â